(untitled) (Swiss Medical Weekly, 2014)
Most hospital-acquired infections arise from colonising bacteria. Intensive care patients and immunocompromised individuals are at highest risk for microbial invasion and subsequent infection due to multiple invasive procedures in addition to frequent application of chemotherapeutics and presence of poor microperfusion leading to mucosal disruption. In this narrative review, we summarise the literature on bacterial colonisation in intensive care patients, in particular the epidemiology, the clinical impact and respective infection control strategies of three pathogens, i.e., Enterococcusspp., extended-spectrum ß-lactamase producing gram-negative bacteria and Clostridium difficile, which have evolved from commensals to a public health concern today.